Cos x x csc2 x cot x1 x csc2 x cot x cot x because

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = 3. The function is y = 3x2 − x − 2. dy 58. Let P (x0 , y0 ) be the point where y = x2 + k is tangent to y = 2x. The slope of the curve is = 2x dx and the slope of the line is 2 thus at P , 2x0 = 2 so x0 = 1. But P is on the line, so y0 = 2x0 = 2. Because P is also on the curve we get y0 = x2 + k so k = y0 − x2 = 2 − (1)2 = 1. 0 0 59. The points (−1, 1) and (2, 4) are on the secant line so its slope is (4 − 1)/(2 + 1) = 1. The slope of the tangent line to y = x2 is y = 2x so 2x = 1, x = 1/2. 60. The √ points (1, 1) and (4, 2) are on the secant√ so its slope is 1/3. The slope of the tangent line to line √ √ y = x is y = 1/(2 x) so 1/(2 x) = 1/3, 2 x = 3, x = 9/4. 61. y = −2x, so at any point (x0 , y0 ) on y = 1 − x2 the tangent line is y − y0 = −2x0 (x − x0 ), or to y = −2x0 x + x2 + 1. The point (2, 0) is√ be on the line, so 0 = −4x0 + x2 + 1, x2 − 4x0 + 1 = 0. Use 0 0 0 √ 4 ± 16 − 4 = 2 ± 3. the quadratic formula to get x0 = 2 62. Let P1 (x1 , ax2 ) and P2 (x2 , ax2 ) be the points of tangency. y = 2ax so the tangent lines at P1 and P2 1 2 are y − ax2 = 2ax1 (x − x1 ) and y − ax2 = 2ax2 (x − x2 ). Solve for x to get x = 1 (x1 + x2 ) which is the 1 2 2 x-coordinate of a point on the vertical line halfway between P1 and P2 . 63. y = 3ax2 + b; the tangent line at x = x0 is y − y0 = (3ax2 + b)(x − x0 ) where y0 = ax3 + bx0 . Solve 0 0 with y = ax3 + bx to get (ax3 + bx) − (ax3 + bx0 ) = (3ax2 + b)(x − x0 ) 0 0 ax3 + bx − ax3 − bx0 = 3ax2 x − 3ax3 + bx − bx0 0 0 0 x3 − 3x2 x + 2x3 = 0 0 0 (x − x0 )(x2 + xx0 − 2x2 ) = 0 0 (x − x0 )2 (x + 2x0 ) = 0, so x = −2x0 . 64. Let (x0 , y0 ) be the point of tangency. Refer to the solution to Exercise 65 to see that the endpoints of the line segment are at (2x0 , 0) and (0, 2y0 ), so (x0 , y0 ) is the midpoint of the segment. 77 65. Chapter 3 1 1 x 2 ; the tangent line at x = x0 is y − y0 = − 2 (x − x0 ), or y = − 2 + . The tangent line x2 x0 x0 x0 1 crosses the x-axis at 2x0 , the y -axis at 2/x0 , so that the area of the triangle is (2/x0 )(2x0 ) = 2. 2 y =− 66. f (x) = 3ax2 + 2bx + c; there is a horizontal tangent where f (x) = 0. Use the quadratic formula on √ 3ax2 + 2bx + c = 0 to get x = (−b ± b2 − 3ac)/(3a) which gives two real solutions, one real solution, or none if (b) b2 − 3ac = 0 (c) b2 − 3ac < 0 (a) b2 − 3ac > 0 67. F = GmM r−2 , dF 2GmM = −2GmM r−3 = − dr r3 68. dR/dT = 0.04124 − 3.558 × 10−5 T which decreases as T increases from 0 to 700. When T = 0, dR/dT = 0.04124 Ω/◦ C; when T = 700, dR/dT = 0.01633 Ω/◦ C. The resistance is most sensitive to temperature changes at T = 0◦ C, least sensitive at T = 700◦ C. 69. f (x) = 1 + 1/x2 > 0 for all x 6 -6 6 -6 70. x2 − 4 ; (x2 + 4)2 f (x) > 0 when x2 < 4, i.e. on −2 < x < 2 1.5 f (x) = −5 -5 5 -1.5 71. (f · g · h) = [(f · g ) · h] = (f · g )h + h(f · g ) = (f · g )h + h[f g + f g ] = f gh + f g h + f g h 72. (f1 f2 · · · fn ) = (f1 f2 · · · fn ) + (f1 f2 · · · fn ) + · · · + (f1 f2 · · · fn ) 73. (a) 2(1 + x−1 )(x−3 + 7) + (2x + 1)(−x−2 )(x−3 + 7) + (2x + 1)(1 + x−1 )(−3x−4 ) (b) (x7 + 2x − 3)3 = (x7 + 2x − 3)(x7 + 2x − 3)(x7 + 2x − 3) so d7 (x + 2x − 3)3 = (7x6 + 2)(x7 + 2x − 3)(x7 + 2x − 3) dx +(x7 + 2x − 3)(7x6 + 2)(x7 + 2x − 3) +(x7 + 2x − 3)(x7 + 2x − 3)(7x6 + 2) = 3(7x6 + 2)(x7 + 2x − 3)2 74. (a) −5x−6 (x2 + 2x)(4 − 3x)(2x9 + 1) + x−5 (2x + 2)(4 − 3x)(2x9 + 1) +x−5 (x2 + 2x)(−3)(2x9 + 1) + x−5 (x2 + 2x)(4 − 3x)(18x8 ) Exercise Set 3.3 (b) 75. 78 (x2 + 1)50 = (x2 + 1)(x2 + 1) · · · (x2 + 1), where (x2 + 1) occurs 50 times so d2 (x + 1)50 = [(2x)(x2 + 1) · · · (x2 + 1)] + [(x2 + 1)(2x) · · · (x2 + 1)] dx + · · · + [(x2 + 1)(x2 + 1) · · · (2x)] = 2x(x2 + 1)49 + 2x(x2 + 1)49 + · · · + 2x(x2 + 1)49 = 100x(x2 + 1)49 because 2x(x2 + 1)49 occurs 50 times. f is continuous at 1 because lim− f (x) = lim+ f (x) = f (1), also lim− f (x) = lim− 2x = 2 and x→1 x→1 1 1 lim+ f (x) = lim+ √ = so f is not differentiable at 1. x→1 x→1 2 x 2 x→1 x→1 76. f is continuous at 1/2 because lim − f (x) = lim + f (x) = f (1/2), also x→1/2 x→1/2 2 lim f (x) = lim − 3x = 3/4 and lim + f (x) = lim + 3x/2 = 3/4 so f (1/2) = 3/4. x→1/2− x→1/2 x→1/2 x→1/2 77. If f is differentiable at x = 1, then f is continuous there; lim+ f (x) = lim− f (x) = f (1) = 3, a + b = 3; lim+ f (x) = a and x→1 x→1 x→1 lim− f (x) = 6 so a = 6 and b = 3 − 6 = −3. x→1 78. (a) lim f (x) = lim− 2x = 0 and lim+ f (x) = lim+ 2x = 0; f (0) does not exist because f is not x→0− x→0 x→0 x→0 continuous at x = 0. (b) lim− f (x) = lim+ f (x) = 0 and f is continuous at x = 0, so f (0) = 0; x→0 x→0 lim− f (x) = lim− (2) = 2 and lim+ f (x) = lim+ 6x = 0, so f (0) does not exist. x→0 79. (a) x→0 x→0 x→0 f (x) = 3x − 2 if x ≥ 2/3, f (x) = −3x + 2 if x < 2/3 so f is differentiable everywhere except perhaps at 2/3. f is continuous at 2/3, also lim − f (x) = lim − (−3) = −3 and lim + f (x) = x→2/3 x→2/3 x→2/3 lim + (3) = 3 so f is not differentiable at x = 2/3. x→2/3 (b) f (x) = x2 − 4 if |x| ≥ 2, f (x...
View Full Document

This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online